2018
DOI: 10.3390/languages3030027
|View full text |Cite
|
Sign up to set email alerts
|

Language Dominance, Verbal Fluency, and Language Control in two Groups of Russian–English Bilinguals

Abstract: This study explored language dominance, verbal fluency, and language control abilities of two groups of younger and older Russian-English bilinguals who had spent similar amounts of time as immigrants in the U.S. Verbal fluency tasks (based on letter and semantic cues, including a new method to elicit parallel letter-fluency data for Russian and English) were used to measure the bilinguals' current lexical retrieval skills in addition to self-assessments of language proficiencies at time of study and time of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The cognitive effects of bilingualism have been investigated from the 1920s’ and onward, with early research often neglecting to account for factors that have later been shown to be relevant, such as rural–urban differences, gender, socioeconomics and proficiency ( Adesope et al., 2010 ; Peal & Lambert, 1962 ). Several methods to measure the balance between L1 and L2 have been suggested; for example dividing word flow in L1 by word flow in L2 ( Erdodi et al., 2017 ; Peal & Lambert, 1962 ; Shishkin & Ecke, 2018 ; Suarez, Gollan, Heaton, Grant, & Cherner, 2014 ). However, when dividing word flow between L1 and L2, current L1 capacity should be considered, as first language (L1) maintenance has been shown to be a factor ( Shishkin & Ecke, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cognitive effects of bilingualism have been investigated from the 1920s’ and onward, with early research often neglecting to account for factors that have later been shown to be relevant, such as rural–urban differences, gender, socioeconomics and proficiency ( Adesope et al., 2010 ; Peal & Lambert, 1962 ). Several methods to measure the balance between L1 and L2 have been suggested; for example dividing word flow in L1 by word flow in L2 ( Erdodi et al., 2017 ; Peal & Lambert, 1962 ; Shishkin & Ecke, 2018 ; Suarez, Gollan, Heaton, Grant, & Cherner, 2014 ). However, when dividing word flow between L1 and L2, current L1 capacity should be considered, as first language (L1) maintenance has been shown to be a factor ( Shishkin & Ecke, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods to measure the balance between L1 and L2 have been suggested; for example dividing word flow in L1 by word flow in L2 ( Erdodi et al., 2017 ; Peal & Lambert, 1962 ; Shishkin & Ecke, 2018 ; Suarez, Gollan, Heaton, Grant, & Cherner, 2014 ). However, when dividing word flow between L1 and L2, current L1 capacity should be considered, as first language (L1) maintenance has been shown to be a factor ( Shishkin & Ecke, 2018 ). Several bilingual varieties have been suggested (balanced, early, late, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Bahrick et al, 1994;Dunn & Fox Tree, 2009;Gertken et al, 2014). Phonological fluency as a measure of language dominance in the spoken modality has been reported at least in Shishkin & Ecke (2018). Whether these recent advances in research on language dominance in spoken languages, albeit mainly in European and North American contexts (Treffers-Daller, 2019), are distinctive to the spoken modality is a question that has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…However, these people do not fit the quite tight category of natural or balanced bilinguals and for decades stayed unnoticed by the scholars studying bilingualism [7]. More recent studies though have examined the subject matter in more detail [3,5,6,9]. The research at large aims to continue closing the gap and study late Russian English bilinguals once it goes full-scale.…”
Section: Introductionmentioning
confidence: 99%